2023
DOI: 10.7759/cureus.35073
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Online Recruitment and an Online Brief Mindfulness Intervention Among Patients With Sickle Cell Disease

Abstract: BackgroundPain among young adult patients with sickle cell disease (PWSCD) is a highly significant public health problem associated with reduced quality of life. Due to issues uniquely affecting PWSCD, including distrust of research, challenging life situations, debilitating pain, stigma, and logistical challenges (e.g., child or elder care and transportation), SCD researchers often find it challenging to meet sample size and enrollment targets. To our knowledge, all known SCD studies have solely recruited par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…With the rise of the pandemic and other factors that may make in-person enrolling difficult, a focus on whether virtual enrollment can be successful has emerged. Our study supports the findings of others, who have found that virtual enrollment can be a successful strategy for recruiting patients with other diseases [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…With the rise of the pandemic and other factors that may make in-person enrolling difficult, a focus on whether virtual enrollment can be successful has emerged. Our study supports the findings of others, who have found that virtual enrollment can be a successful strategy for recruiting patients with other diseases [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…39 Clinical trials assessing ACT and MBSR in people living with SCD are currently still in progress. [40][41][42] As mentioned earlier, clinical trials testing whether positive affect-focused interventions may be useful for reducing opioid use among youth with SCD are needed.…”
Section: Discussionmentioning
confidence: 99%
“…ACT has been associated with reduced pain in other populations, 38 and a case study of 16‐year old with SCD saw improvement in quality of life, but did not see substantial changes in pain and did not assess for changes in opioid use 39 . Clinical trials assessing ACT and MBSR in people living with SCD are currently still in progress 40–42 . As mentioned earlier, clinical trials testing whether positive affect‐focused interventions may be useful for reducing opioid use among youth with SCD are needed.…”
Section: Discussionmentioning
confidence: 99%